2017
DOI: 10.1038/s41598-017-08171-y
|View full text |Cite|
|
Sign up to set email alerts
|

Photonic Spin Hall Effect in Waveguides Composed of Two Types of Single-Negative Metamaterials

Abstract: The polarization controlled optical signal routing has many important applications in photonics such as polarization beam splitter. By using two-dimensional transmission lines with lumped elements, we experimentally demonstrate the selective excitation of guided modes in waveguides composed of two kinds of single-negative metamaterials. A localized, circularly polarized emitter placed near the interface of the two kinds of single-negative metamaterials only couples with one guided mode with a specific propagat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 28 publications
0
36
0
Order By: Relevance
“…Therefore the two kinds of single negative band gap of figures 5(a) and (c) belong to different topological phases, respectively. The topological phase transition can take place when the system converts from effective elasticity negative (ENG) to effective mass negative (MNG), which is similar to the topological change between ENG (ò negative) and MNG (μ negative) in electromagnetism [51][52][53][54].…”
Section: Band Inversion and Zak Phasesmentioning
confidence: 99%
“…Therefore the two kinds of single negative band gap of figures 5(a) and (c) belong to different topological phases, respectively. The topological phase transition can take place when the system converts from effective elasticity negative (ENG) to effective mass negative (MNG), which is similar to the topological change between ENG (ò negative) and MNG (μ negative) in electromagnetism [51][52][53][54].…”
Section: Band Inversion and Zak Phasesmentioning
confidence: 99%
“…5(b) show the enlarged lumped variable capacitance diodes and the protected elements, respectively. Figure 5 C , the effective permittivity and permeability of 2D TLs in the long-wavelength limit can be written as [22,42]:…”
Section: Experimental Demonstration Of the Actively Tunable Topomentioning
confidence: 99%
“…PSHE can be enhanced by metamaterials and metasurfaces. Guo experimentally demonstrated that the PSHE in waveguides with single‐negative metamaterials is robust against interface fluctuations, which may be applicable in the manipulation of electromagnetic signals . The spin‐dependent splitting can also be enhanced by increasing the rotation rate of local optical axes in the metasurfaces .…”
Section: Introductionmentioning
confidence: 99%